Cognitive-Emotional Involvement During Mirror Exposure Is Not Accompanied by Physiological Activation in Binge Eating Disorder - Baur, Julia; Krohmer, Kerstin; Tuschen-Caffier, Brunna; Svaldi, Jennifer (Frontiers in Psychiatry, 2019)
Body image interventions have been shown to reduce self-reported cognitive-emotional facets of body image disturbance in binge eating disorder (BED). However, more objective assessment methods are required to evaluate the effects of these interventions. Therefore, the present study aimed at investigating the usefulness of vocally encoded emotional arousal as physiological correlate of body dissatisfaction during mirror exposure in women with BED. Women with BED (n = 60) and weight-matched controls (CG; n = 60) participated in an experimental thought-sampling procedure including a mirror exposure and a control condition in a repeated-measures design. Fundamental frequency as a vocal correlate of emotional arousal as well as negative, neutral and positive body-related cognitions during both conditions were analyzed. In line with our hypotheses, the BED group verbalized more negative and less positive and neutral body-related cognitions during the mirror exposure condition compared to the CG. Contrary to our hypotheses, though, there was a stronger increase in physiological arousal between the control and the mirror exposure condition in the CG relative to the BED group. Furthermore, a significant negative correlation between fundamental frequency and the severity of cognitive-emotional body image disturbances emerged. The findings indicate a cognitive-emotional over-involvement with physical appearance during mirror exposure in women with BED compared to weight-matched controls in the absence of a corresponding physiological pattern. Results are discussed in terms of an impaired ability of women with BED to show adequate physiological responses to body-related stress. In addition, methodological recommendations for future research are presented.